Electronic Structures and Structural Evolution of Hydrogenated Graphene Probed by Raman Spectroscopy - Luo, Zhiqiang; Yu, Ting; Ni, Zhenhua; Lim, Sanhua; Hu, Hailong; Shang, Jingzhi; Liu, Lei; Shen, Zexiang; Lin, Jianyi (Journal of physical chemistry. C, 2011)
The electronic structures and structural evolution of hydrogenated graphene are investigated by Raman spectroscopy with multiple excitations. The excitation energy dependent saturation effect on the ratio of integrated intensities of D and G modes (I D/I G) is revealed and interpreted by a D band active model with D band Raman relaxation length and photoexcited electron/hole wavelength as critical length scales. At low hydrogen coverage, the chemisorbed H atoms behave like defects in sp2 CC matrix; for a high hydrogen coverage, the sp3 C−H bonds become coalescent clusters resulting in confinement effect on the sp2 C domains. Electronic structure changes caused by varying hydrogen coverage are evidenced by excitation energy dependent red shift of D and 2D bands. Our results provide a useful guide for developing applications of hydrogenated graphene as well as for using Raman spectroscopy for quick characterization in further exploring other kinds of graphene derivatives.